Definitions for "palliative care", "end-of-life" and "terminally ill" in oncology: a scoping review - Franciele Roberta Cordeiro; Stefanie Griebeler Oliveira; Juliana Zeppini Giudice; Vanessa Pellegrini Fernandes; Adriéli Timm Oliveira (Universidad Católica del Uruguay, 2020)
Objective: to identify and map the definitions for palliative care, end of life, and terminally ill in the oncology literature. Materials and method: scoping review guided by Joanna Brigs Institute recommendations. We analyzed original articles, published between 2012 and 2017, indexed in the databases Pubmed, Web of Science and Scopus. The data collection resulted in 51 articles selected for analysis. Also, we have consulted the websites of 25 palliative care societies from countries best ranked in The Economist's Quality of Death Ranking. The data were analyzed through descriptive statistics, and summary of the themes, in this case the definitions. Results: terminally ill is a disease with a prognosis of lifetime ranging between hours and months, there is clinical worsening, functional decline, and presence of metastases. Palliative care aims to promote quality of life and dignity. End of life is the period of up to 12 months before death. Conclusions: we constructed synthesis and definitions for the concepts investigated. Thus, it was possible to contribute to the adoption of a standardized language in care and investigations with cancer patients in end-of-life